Mapové fondy vojsk tří císařů v Bitvě u Slavkova 2. prosince 1805 - Gabrlík, Marek (Vysoké učení technické v Brně. Fakulta stavební, 2014)
Úvodní část mé práce se zabývá historií Bitvy tří císařů. Popisuje významné historické události, které k bitvě vedly, průběh bitvy a její důsledky ,vyplývající z francouzského vítězství. Hlavní část se věnuje mapovým fondům vojsk tří císařů. Zkoumá je z hlediska historie, porovnávání topografických a geografických údajů a postupu vedení bitvy.

The opening part of my work deals with the history of the Battle of the Three Emperors. Describes the major historical events that led to the battle, procedure of the Battle of Austerlitz and its consequences ,resulting from the french victory. The main part is devoted to mapping funds of troops of the Three Emperors. Examines them in terms of history, comparing topographic and geographic data and procedure of battle management.
The Maps Fundsof Army three Emferors in Battle at Austerlitz 02.12.1805
Keywords: Bitva tří císařů; 2. prosince 1805; mapy; Slavkov; Battle of the three emperors; 2nd December 1805; maps; Austerlitz